Cover glass with outer frame, semiconductor light-emitting device, and semiconductor light-receiving device

By directly bonding the outer frame made of borosilicate glass ceramic with flat glass and forming a metal film sealing material layer on the outer frame, the problem of difficulty in taking into account both the airtight sealing and verticality in the prior art is solved, glass damage is reduced, drug resistance is improved, and efficient semiconductor device sealing is achieved.

CN119604977APending Publication Date: 2025-03-11AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380056642.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to reduce damage and cracks in flat glass while maintaining airtight sealing and verticality, and the drug resistance is insufficient.

Method used

An outer frame composed of glass ceramics with filler dispersed in borosilicate glass is directly bonded to the flat-shaped glass, and a sealing material layer composed of a metal film is formed on the surface of the outer frame located opposite to the flat-shaped glass side, and an airtight seal is achieved by a gold-tin ring.

Benefits of technology

The good adhesion and perpendicularity between the outer frame and the flat-shaped glass is achieved, damage and cracks of the flat-shaped glass is reduced, and the resistance of the drug-resistant liquid is improved, ensuring the airtight sealing and reliability of the semiconductor light-emitting device and the light-receiving device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604977A_ABST
    Figure CN119604977A_ABST
Patent Text Reader

Abstract

The present invention relates to a cover glass with an outer frame, the cover glass having a flat glass and an outer frame bonded to a first main surface of the flat glass via a glass adhesive layer, the cover glass being characterized in that: boron silicate glass and a filler in a glass ceramic constituting the outer frame both contain alumina, and the volume fraction of the filler in the glass ceramic is 40-65%; the volume fraction of the alumina is 10-65%, and the absolute value of the difference between the average thermal expansion coefficients of the flat glass and the outer frame at 50-350 DEG C is 20 * 10-7 / DEG C or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cover glass with a frame and also to a semiconductor light emitting device and a semiconductor light receiving device hermetically sealed by the cover glass with a frame. Background Art

[0002] Devices using light emitting diodes (LEDs) have been used in a wide range of applications, including backlights for mobile phones and large liquid crystal televisions, and lighting applications.

[0003] For example, in the case of a light emitting device using a light emitting diode (visible light LED) that emits visible light, a structure in which an LED chip is mounted on a flat plate-shaped substrate typified by aluminum nitride and sealed with a resin-based member is often used.

[0004] In contrast, light-emitting devices using ultraviolet light-emitting diodes (UV-LEDs), laser diodes (LDs), vertical cavity surface emitting lasers (VCSELs), etc. require airtight sealing. In addition, VCSELs also require a diffuser plate.

[0005] Therefore, these light emitting devices need to have a shape in which the outer frame is provided with a cover glass. Although the outer frame can also be provided on a substrate such as aluminum nitride, it is realistic to provide the outer frame on the cover glass from the aspect of cost.

[0006] In addition to the above-mentioned light-emitting devices, there are also cases where airtight sealing is required in light-receiving devices such as sensors. For example, there is a device called MEMS (MicroElectro Mechanical Systems) that integrates an electrical circuit and a fine mechanical structure on a substrate. As a substrate used in MEMS, for example, a silicon substrate can be cited.

[0007] In the light receiving device, the cover glass needs to have a frame shape similar to the light emitting device. Although the frame can also be provided on a substrate such as silicon, it is more realistic to provide the frame on the cover glass from the aspect of cost.

[0008] When manufacturing a cover glass with a frame, the simplest method is to separately make the cover glass and the frame glass and bond them together using a resin-based component. However, bonding using an organic resin-based component cannot achieve airtight sealing.

[0009] As a method for obtaining airtight sealing, there is a method of forming an outer frame portion by directly wet etching the glass. However, in addition to being unable to obtain perpendicularity between the flat plate portion and the portion that becomes the outer frame, it is also difficult to make a deep frame. Therefore, in order to obtain airtight sealing while maintaining the perpendicularity, there is a method of directly bonding the flat plate glass and the glass that becomes the outer frame by diffusion bonding, room temperature bonding, etc.

[0010] On the other hand, direct bonding is very costly, and therefore, technologies for providing a frame on a glass substrate have been studied and proposed from various perspectives.

[0011] For example, Patent Document 1 discloses a synthetic quartz glass chamber formed by attaching another raw synthetic quartz glass substrate to a raw synthetic quartz glass substrate having a plurality of through holes formed therein by sandblasting and bonding them at 1000 to 1200°C.

[0012] Patent Document 2 discloses a framed anti-reflection glass in which a silicon substrate having through holes formed by reactive ion etching is overlapped as a frame-shaped member on a borosilicate glass as a flat plate-shaped member and anodically bonded.

[0013] Patent Document 3 discloses a glass sealing material in which a glass plate and a glass sheet are sandwiched between a bottom mold and a counter mold and joined by welding using a hot press.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent Application Publication No. 2020-21937

[0017] Patent Document 2: Japanese Patent No. 5646981

[0018] Patent Document 3: Japanese Patent Application Publication No. 2013-222522

[0019] Patent Document 4: International Publication No. 2022 / 138519 Summary of the invention

[0020] However, if heat is applied at a temperature exceeding the glass softening point of the glass material used as in the methods described in Patent Documents 1 and 3, the surface of the glass is damaged, and reliability is a concern. If the thermal expansion coefficients of the flat plate-shaped member and the frame-shaped member are different as in the method described in Patent Document 2, there is a risk of cracks in the glass as the flat plate-shaped member. In addition, the cost of anodic bonding is also high.

[0021] In contrast, the present inventors proposed a new cover glass with a frame in which a frame made of a specific glass ceramic is directly bonded to a flat glass as disclosed in Patent Document 4. This can achieve both verticality when the frame has a height of a certain value or more and adhesion to the cover glass, and can also reduce damage and cracks on the surface of the flat glass.

[0022] However, the inventors of the present invention have further studied and found that when a flat glass sheet is directly bonded to an outer frame, there is hope for improvement in chemical liquid resistance.

[0023] Therefore, an object of the present invention is to provide a cover glass with a frame which has both the adhesion between the frame and the plate glass and the verticality of the frame, reduces scratches and cracks on the surface of the plate glass, and has excellent resistance to chemical liquids.

[0024] In order to solve the above-mentioned problems, one aspect of the cover glass with a frame according to the present embodiment is as follows.

[0025] A cover glass with a frame comprises: a flat glass having a first main surface and a second main surface facing each other, and a frame bonded to the first main surface of the flat glass via a glass adhesive layer.

[0026] The outer frame is made of glass ceramics in which fillers are dispersed in borosilicate glass.

[0027] The borosilicate glass and the filler both contain aluminum oxide.

[0028] The volume fraction of the filler in the glass ceramic is 40 to 65%.

[0029] The volume fraction of the aluminum oxide contained in the filler in the glass ceramic is 10 to 65%.

[0030] The absolute value of the difference between the average thermal expansion coefficient of the plate-shaped glass and the outer frame at 50 to 350°C is 20×10 -7 / ℃ below.

[0031] In addition, one aspect of the semiconductor light emitting device according to the present embodiment is as follows.

[0032] A semiconductor light emitting device comprises: a cover glass with an outer frame, a substrate, and a light emitting element arranged on the substrate.

[0033] The cover glass with a frame is integrated with the substrate via a sealing material layer composed of a metal film and a gold tin ring in the cover glass with a frame, so that the light emitting element is hermetically sealed.

[0034] It should be noted that the cover glass with a frame is the cover glass with a frame described above as one embodiment, and the cover glass with a frame further has a sealing material layer composed of a metal film on the surface of the frame located on the side opposite to the flat glass side, and the metal film has an Ag layer or an Au layer on its outermost surface.

[0035] In addition, one aspect of the semiconductor light receiving device of the present embodiment is as follows.

[0036] A semiconductor light receiving device comprises: a cover glass with an outer frame, a substrate, and a light receiving element arranged on the substrate.

[0037] The cover glass with a frame is integrated with the substrate via a sealing material layer composed of a metal film and a gold tin ring in the cover glass with a frame, and the light receiving element is hermetically sealed.

[0038] According to the cover glass with an outer frame of the present invention, it is possible to have both the close fit between the outer frame and the flat glass and the verticality of the outer frame, and prevent the cover glass from being damaged by the energy of UV-LED, LD (laser diode) and the like as the light source, the light energy received by the sensor, and the like. In addition, since there is no damage or cracks on the surface of the flat glass caused by heat, the reliability of the cover glass with an outer frame is very high. In addition to airtight sealing, this reliability is also based on the viewpoints of resistance under high temperature and high humidity, thermal shock, verticality, etc. In addition, since the resistance to chemical liquid is very good, the durability is excellent. From these viewpoints, an excellent semiconductor light-emitting device and semiconductor light-receiving device that are airtightly sealed using the cover glass with an outer frame of the present invention are obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a cross-sectional schematic diagram showing an example of the cover glass with a frame according to the present embodiment.

[0040] Figure 2 It is a cross-sectional schematic diagram showing an example of the cover glass with a frame according to the present embodiment.

[0041] Figure 3 It is a cross-sectional schematic diagram showing an example of the cover glass with a frame according to the present embodiment.

[0042] Figure 4 It is a cross-sectional schematic diagram showing an example of the cover glass with a frame according to the present embodiment.

[0043] Figure 5 1 is a schematic cross-sectional view showing an example of a cover glass with a frame according to the present embodiment. Figure 5 (a) is an example in which antireflection films are provided on both main surfaces of the flat glass. Figure 5(b) is an example in which antireflection films are provided on both main surfaces of the flat glass having the light diffusion portion on the first main surface. DETAILED DESCRIPTION

[0044] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.

[0045] In the present specification, “to” indicating a numerical range is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0046] The “average thermal expansion coefficient” or “thermal expansion coefficient” in this specification refers to a value measured as an average value of the ratio of elongation per 1° C. when heating at a heating rate of 5° C. / min in a range of 50 to 350° C. using a dilatometer Dilatometer TD5000SA manufactured by NETZSCH Japan.

[0047] In this specification, the content in the glass matrix refers to the content in the component obtained by removing the filler from the glass ceramic, and is expressed in volume %. The content of various components contained in the glass matrix is ​​a value expressed in mass % based on the oxide standard. In addition, "mass %" and "weight %" have the same meaning.

[0048] In addition, the content of filler in glass ceramics refers to the content obtained by removing the glass component, i.e., the glass matrix, from the glass ceramics, and is a value expressed in volume %. Volume % is a value obtained by mass % and the specific gravity of various components. When the mass % of the glass matrix is ​​set to M1, the specific gravity is set to ρ1, the mass % of the filler is set to M2, and the specific gravity is set to ρ2, the volume % of the glass matrix and the volume % of the filler are obtained from the content expressed in mass % using the following formula.

[0049] Volume % of glass matrix = (M1 / ρ1) / (M1 / ρ1+M2 / ρ2)

[0050] Volume % of filler = (M2 / ρ2) / (M1 / ρ1+M2 / ρ2)

[0051] The volume % of the glass ceramic after sintering can be calculated from the mass % and specific gravity based on oxides determined by energy dispersive X-ray spectroscopy (EDX) or inductively coupled plasma emission spectroscopy (ICP).

[0052] <Cover glass with frame>

[0053] like Figure 1 As shown, the cover glass with outer frame 10 of this embodiment has an outer frame 2 bonded to a first main surface 1a of a sheet glass 1 via a glass adhesive layer 3. The sheet glass 1 is bonded to the outer frame 2 along the outer edge.

[0054] The outer frame 2 is made of glass ceramics in which a filler is dispersed in borosilicate glass as a glass matrix, and both the borosilicate glass and the filler contain aluminum oxide.

[0055] The volume fraction of the filler in the glass ceramic is 40 to 65%, and the volume fraction of the aluminum oxide contained in the filler in the glass ceramic is 10 to 65%.

[0056] The absolute value of the difference between the average thermal expansion coefficient of the flat glass and the outer frame at 50-350°C is 20×10 -7 / ℃ below.

[0057] Flat glass

[0058] The sheet glass 1 has a first main surface 1 a and a second main surface 1 b facing each other, and an outer frame 2 is bonded to the first main surface 1 a via a glass adhesive layer 3 .

[0059] The plate glass 1 and the outer frame 2 have an absolute value of a difference in average thermal expansion coefficient at 50 to 350°C of 20×10 -7 / °C or less, but is preferably 20×10 -7 ~99×10 -7 / °C, more preferably 25×10 -7 ~90×10 -7 / ℃, more preferably 30×10 -7 ~80×10 -7 / °C. Here, the lower limit is preferably 20×10 -7 / °C or more, more preferably 25×10 -7 / ℃ or more, more preferably 30×10 -7 / °C or more. In addition, the upper limit is preferably 99×10 -7 / °C or less, more preferably 90×10 -7 / °C or less, more preferably 80×10 -7 / ℃ below.

[0060] The glass transition temperature Tg of the flat glass 1 is preferably higher than the softening point Ts of the glass adhesive layer 3. Specifically, from the viewpoint of suppressing the increase of carbon residue during calcination and the loss of insulation, and from the viewpoint of heat resistance during sealing with the substrate, the glass transition temperature Tg of the flat glass 1 is more preferably 500°C or higher, further preferably 515°C or higher, and further preferably 520°C or higher, and the higher the better. It should be noted that the glass transition temperature Tg of the flat glass 1 is the temperature at the first inflection point of the DTA curve obtained by differential thermal analysis (DTA).

[0061] From the viewpoint of preventing damage to the surface of the flat glass, the glass softening point Ts of the flat glass 1 is preferably 700° C. or higher, more preferably 715° C. or higher, and further preferably 730° C. or higher, the higher the better. The glass softening point Ts of the flat glass 1 is the temperature at the fourth inflection point of the DTA curve.

[0062] Specifically, the flat glass 1 is preferably transparent from the visible light region to the near infrared region, and for example, soda-lime glass, borosilicate glass, aluminum silicate glass, quartz glass, sapphire glass, etc. can be used. From the aspect of easy processing, borosilicate glass is preferred. In addition, from the aspect of durability and transmittance, quartz glass is preferred.

[0063] The thickness of the flat glass 1 is not particularly limited, but is preferably 200 μm to 1.5 mm, more preferably 250 μm to 1.2 mm, and even more preferably 300 μm to 1.1 mm. Here, from the viewpoint of durability, the thickness of the flat glass is preferably 200 μm or more, more preferably 250 μm or more, and even more preferably 300 μm or more. On the other hand, from the viewpoint of transmittance and weight, the thickness of the flat glass 1 is preferably 1.5 mm or less, more preferably 1.2 mm or less, and even more preferably 1.1 mm or less.

[0064] The flat glass 1 may include a light diffusion portion on at least one of the first main surface 1a and the second main surface 1b. Figure 2 As shown, a light diffusion portion 1c may be provided on the first main surface 1a. The light diffusion portion 1c is preferably formed by direct processing of the first main surface 1a of the flat glass 1. It should be noted that a separate light diffusion layer may be provided instead of a directly processed light diffusion portion. In this case, from the viewpoint of airtight sealing, the light diffusion layer is preferably composed of an inorganic material.

[0065] The light diffusion portion 1 c formed by directly processing the sheet glass 1 is preferred from the viewpoint of reducing loss due to interface reflection and preventing interlayer delamination, compared with forming a separate light diffusion layer on the first main surface 1 a of the sheet glass 1 .

[0066] From the viewpoint of the close adhesion between the flat glass 1 and the outer frame 2, the light diffusion portion 1c is preferably formed on the inner side of the region on the first main surface 1a of the flat glass 1 to which the outer frame 2 is bonded via the glass adhesive layer 3. In addition, when such direct processing is performed, for example, EN-A1 (trade name), M100 (trade name), M130 (trade name) manufactured by AGC, TEMPAX (registered trademark), D263 (registered trademark) manufactured by SCHOTT, etc. can be preferably used for the flat glass, but it is not limited thereto.

[0067] The light diffusion portion 1 c preferably includes a plurality of lenses, more preferably has a clear boundary between adjacent lenses, and is further preferably arranged without gaps in at least the effective region on the first main surface 1 a of the sheet glass 1 .

[0068] Outer Frame

[0069] The outer frame 2 is made of glass ceramics in which a filler is dispersed in borosilicate glass.

[0070] By including borosilicate glass as the glass matrix, the chemical liquid resistance of the glass ceramic becomes extremely high.

[0071] The present inventors have found that when both the borosilicate glass and the filler contain aluminum oxide, the wettability between the borosilicate glass as a glass matrix and the filler is improved, and the sinterability is improved. As a result, the airtight sealing property of the cover glass with a frame becomes very good.

[0072] Borosilicate glass refers to glass containing boron oxide (B2O3) and silicate (SiO2) in its glass composition, but the glass softening point Ts of glass ceramics is lowered by containing boron oxide. In addition, silicate is a component constituting glass.

[0073] The content of boron oxide in the glass matrix constituting the glass ceramic is not particularly limited, and is, for example, preferably 5 to 50% by mass, more preferably 10 to 30% by mass, and further preferably 15 to 20% by mass. Here, the lower limit of the content of boron oxide is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. On the other hand, from the viewpoint of suppressing the reduction in weather resistance of the flat glass 1, the content of boron oxide is preferably 50% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less.

[0074] The content of silicate in the glass matrix constituting the glass ceramic is not particularly limited, for example, preferably 30 to 85% by mass, more preferably 40 to 80% by mass, and further preferably 45 to 75% by mass. Here, from the viewpoint of weather resistance, the lower limit of the content of silicate is preferably 30% by mass or more, more preferably 40% by mass or more, and further preferably 45% by mass or more. On the other hand, from the viewpoint of preventing the glass softening point Ts from becoming too high, the content of silicate is preferably 85% by mass or less, more preferably 80% by mass or less, and further preferably 75% by mass or less.

[0075] The content of aluminum oxide in the glass matrix constituting the glass ceramic is not particularly limited, and for example, is preferably 0.5 to 25% by mass, more preferably 1 to 20% by mass, and further preferably 1.5 to 17% by mass. Here, from the viewpoint of obtaining good sinterability, the lower limit of the content of aluminum oxide is preferably 0.5% by mass or more, more preferably 1% by mass or more, and further preferably 1.5% by mass or more. On the other hand, from the viewpoint of preventing easy devitrification and the glass softening point Ts from becoming too high, the content of aluminum oxide is preferably 25% by mass or less, more preferably 20% by mass or less, and further preferably 17% by mass or less.

[0076] It should be noted that the aluminum oxide in the glass matrix is ​​clearly distinguished from the aluminum oxide as a filler. That is, the content of the aluminum oxide as a glass component is excluded from the content of the inorganic powder containing the aluminum oxide as a filler.

[0077] Borosilicate glass may contain CeO2, RO, R'2O, R"2O3, R"'O2, etc. in addition to SiO2, B2O3 and Al2O3. Here, R in this specification refers to at least one selected from Zn, Ba, Sr, Mg, Ca, Fe, Mn, Cr, Sn and Cu. R' refers to at least one selected from Li, Na, K, Cs and Cu. R" refers to at least one of Fe and La. R"' refers to at least one selected from Zr, Ti and Sn.

[0078] The glass matrix preferably further contains, for example, ZnO, K2O, and Na2O among the above.

[0079] More specifically, as the borosilicate glass, for example, glass containing 50 to 70% by mass of SiO 2 , 15 to 20% by mass of B 2 O 3 , 2 to 15% by mass of Al 2 O 3 , and 5 to 25% by mass of CaO is preferably used.

[0080] The components of the borosilicate glass other than boron oxide (B2O3), silicon (SiO2) and aluminum oxide (Al2O3) are described below.

[0081] CeO2 is a component that stabilizes the color tone of the glass powder after the glass raw material is melted and vitrified. On the other hand, if excessively added, it is likely to be easily crystallized, and it is difficult to obtain a stable glass powder.

[0082] The components represented by RO including CaO are effective for stabilizing the glass and suppressing crystallization. On the other hand, if excessively added, the softening point Ts of the glass may become too high.

[0083] The components represented by R'2O including K2O and Na2O are components that lower the softening point Ts of glass. The smaller the atomic number of the element, the greater the effect. However, if the content of the element with a smaller atomic number increases, the insulation of the glass may decrease, which may damage the reliability.

[0084] The component represented by R"2O3 is effective for stabilizing the glass, and improves the effect of inhibiting crystallization and the chemical durability of the glass. On the other hand, if it is added in excessive amount, the softening point Ts of the glass may become too high.

[0085] The component represented by R"'O2 is a component that supplies oxygen during bonding. On the other hand, if it is added in excess, there is a possibility of foaming during bonding.

[0086] The glass softening point Ts of the borosilicate glass is, for example, preferably 700 to 1000°C, more preferably 750 to 900°C, and further preferably 800 to 850°C. Here, from the viewpoint of sinterability of glass ceramics, the glass softening point Ts of the borosilicate glass is preferably 1000°C or less, more preferably 900°C or less, and further preferably 850°C or less. In addition, from the viewpoint of heat resistance, the glass softening point Ts of the borosilicate glass is preferably 700°C or more, more preferably 750°C or more, and further preferably 800°C or more. It should be noted that the glass softening point Ts of the borosilicate glass is the temperature at the fourth inflection point of the DTA curve of the glass alone.

[0087] The filler in the glass ceramic is dispersed in the borosilicate glass serving as the glass matrix. The filler contains alumina, thereby improving wettability with the glass component in the glass ceramic and improving sinterability.

[0088] The volume fraction of the filler in the glass ceramic is 40 to 65%, preferably 41 to 63%, and more preferably 42 to 61%. Here, the glass ceramic has strength as the outer frame 2, and from the viewpoint of maintaining perpendicularity to the flat glass 1, the above volume fraction is 40% or more, preferably 41% or more, and more preferably 42% or more. In addition, from the viewpoint of achieving good sintering properties of the outer frame 2 and good adhesion when the glass ceramic is bonded to the flat glass 1 via the glass adhesive layer, the above volume fraction is 65% or less, preferably 63% or less, and more preferably 61% or less.

[0089] In addition, when the inorganic powder other than alumina is included as a filler, that is, when two or more kinds of inorganic powders are included, the above-mentioned volume fraction is the total volume fraction of these.

[0090] The volume fraction of aluminum oxide contained in the filler in the glass ceramic is 10 to 65%, preferably 11 to 63%, and more preferably 12 to 61%. Here, from the perspective of wettability with the glass component in the glass matrix and strength, the above volume fraction is 10% or more, preferably 11% or more, and more preferably 12% or more. In addition, the filler may also be composed of inorganic powder of aluminum oxide only, that is, the above volume fraction is 65% or less, preferably 63% or less, and more preferably 61% or less.

[0091] The filler may contain inorganic powders other than alumina. Examples of such inorganic powders include negative thermal expansion fillers and low thermal expansion fillers.

[0092] The negative thermal expansion filler is a filler having a negative thermal expansion coefficient, that is, a filler having a thermal expansion coefficient less than 0 / ° C. The negative thermal expansion filler is preferred from the viewpoint of controllability of the thermal expansion coefficient of the outer frame 2 made of glass ceramics.

[0093] For example, a negative thermal expansion filler may have a thermal expansion coefficient of -20×10 -7 / ℃ zirconium phosphate, thermal expansion coefficient is -50×10 -7 / ℃ β-eucryptite (Li2O·Al2O3·2SiO2), thermal expansion coefficient is -7×10 -7 / ℃ zirconium tungstate (ZrW2O8), etc.

[0094] Low thermal expansion filler has a thermal expansion coefficient of 0 to 40×10 -7 / ℃ filler. For low thermal expansion fillers, for example, zirconium oxide, silicon dioxide, and mixtures thereof can be cited. As a mixture, a mixture of magnesium oxide, aluminum oxide, and silicon dioxide, i.e., cordierite (2MgO·2Al2O3·5SiO2), can also be cited as a low thermal expansion filler. Since cordierite contains aluminum oxide, when the filler in this embodiment is composed only of cordierite, aluminum oxide is also included in the filler.

[0095] The filler is an inorganic powder, and its shape is not particularly limited, and examples thereof include spherical, flat, flaky, and fibrous shapes.

[0096] The size of the inorganic powder is not particularly limited, for example, the 50% particle size (D 50 ) is preferably 0.5 to 10 μm, more preferably 1 to 9 μm. Here, the lower limit of the 50% particle size is preferably 0.5 μm or more, more preferably 1 μm or more, and the upper limit of the 50% particle size is preferably 10 μm or less, more preferably 9 μm or less. The 50% particle size is a volume-based cumulative 50% diameter measured using a laser diffraction / scattering particle size distribution measuring device.

[0097] The glass ceramic constituting the outer frame has the filler dispersed in the glass matrix.

[0098] The average thermal expansion coefficient of the outer frame made of glass ceramic at 50 to 350°C is as long as the absolute value of the difference between the average thermal expansion coefficient of the flat glass is 20×10 -7 From the viewpoint of being close to the thermal expansion coefficient of the substrate on which the cover glass 10 with the frame is mounted, the thermal expansion coefficient of the frame is preferably 15×10 -7 ~90×10 -7 / °C or less, although it varies depending on the thermal expansion coefficient of the sheet glass 1, it is more preferably 20×10 -7 ~85×10 -7 / °C, more preferably 25×10 -7 ~80×10 -7 Here, the lower limit of the thermal expansion coefficient is preferably 15×10 -7 / °C or more, more preferably 20×10 -7 / °C or more, more preferably 25×10 -7 / °C or more. In addition, the upper limit of the thermal expansion coefficient is preferably 90×10 -7 / °C or less, more preferably 85×10 -7 / °C or less, more preferably 80×10 -7 / ℃ below.

[0099] The glass ceramic forming the outer frame 2 in this embodiment has an absolute value of a difference in average thermal expansion coefficient between the plate-shaped glass 1 and the outer frame 2 at 50 to 350° C. of 20×10 -7 / °C or less. Thus, when the outer frame 2 and the sheet glass 1 are bonded via the glass adhesive layer, it is possible to suppress the occurrence of damage or cracks on the sheet glass 1 due to expansion mismatch.

[0100] The absolute value of the difference between the above average thermal expansion coefficients is 20×10 -7 / ℃ or less, preferably 18×10 -7 / °C or less, more preferably 15×10 -7 / ℃ or below, the closer to 0 / ℃ the better.

[0101] From the viewpoint of adhesion with a substrate having a light emitting element, a light receiving element, etc., the maximum height roughness Rz of the surface of the outer frame 2 located on the side opposite to the flat glass 1 side is preferably 5 μm or less, more preferably 4.5 μm or less, and further preferably 4 μm or less. Since the maximum height roughness Rz of the glass ceramic obtained by calcining the precursor of the glass ceramic is generally about 10 μm, the maximum height roughness Rz can be reduced to 5 μm or less by performing a flattening process such as grinding.

[0102] It should be noted that the maximum height roughness Rz in this specification is an index of surface roughness, which refers to the sum of the height of the highest peak and the depth of the deepest valley in the profile curve of the reference length, and is obtained in accordance with JIS B 0601: 2001. Specifically, the maximum height roughness Rz is a value obtained by measuring a measurement length of 3 mm with a wavelength of 0.8 mm using a surface roughness and profile measuring instrument Surfcom.

[0103] From the viewpoint of the use of the cover glass 10 with an outer frame and the effective use of space, it is preferred that the outer frame 2 is joined perpendicularly to the plate-shaped glass 1. The plate-shaped glass 1 and the outer frame 2 are perpendicular to each other, which means that the angle formed by the outer surface of the plate-shaped glass 1 and the outer frame 2 is perpendicular. It should be noted that the perpendicularity does not need to be strictly 90°, and it is sufficient as long as it is approximately perpendicular to 90°±5°.

[0104] The height of the outer frame 2 is preferably 350 μm to 4 mm, more preferably 400 μm to 3.5 mm, and further preferably 500 μm to 3 mm. Here, from the viewpoint of preventing the cover glass from being damaged by light energy from the light source, the height of the outer frame 2 is preferably 350 μm or more, more preferably 400 μm or more, and further preferably 500 μm or more. On the other hand, from the requirement of low height of the device, the height of the outer frame 2 is preferably 4 mm or less, more preferably 3.5 mm or less, and further preferably 3 mm or less.

[0105] Since the height can be adjusted by changing the number of layers, and a higher frame can be formed as needed, the outer frame 2 is preferably a calcined body of stacked green sheets. The details of the green sheet will be described later, and the green sheet refers to a sheet formed by dispersing a powder as a glass ceramic precursor in a binder, etc., and then casting.

[0106] Glass bonding layer

[0107] The glass adhesive layer 3 is a layer for bonding the plate-shaped glass 1 and the outer frame 2 .

[0108] The glass adhesive layer 3 is different from an adhesive layer of an organic material such as a resin layer, and is made of glass, so it has excellent durability. In addition, when a conductive film 5 of an inorganic material described later is formed on the first main surface 1a of the flat glass 1, the flat glass 1 is joined to the outer frame 2 via the conductive film 5 in addition to the glass adhesive layer 3. In this case, the conductive film 4 is regarded as a structure made of an inorganic material that is integrated with the flat glass 1, and is a method of joining the flat glass 1 to the outer frame 2 via the glass adhesive layer 3.

[0109] The softening point Ts of the glass adhesive layer 3 is preferably lower than the softening point Ts of the borosilicate glass of the glass matrix of the glass ceramic of the frame 2, and lower than the glass transition temperature Tg of the flat glass 1. By lowering the softening point Ts of the glass adhesive layer 3 as described above, the flat glass 1 and the outer frame 2 can be bonded at a low temperature without causing damage or cracks to the flat glass 1.

[0110] The softening point Ts of the glass adhesive layer 3 varies depending on the softening point Ts of the borosilicate glass in the outer frame 2 and the glass transition temperature Tg of the flat glass 1, but is preferably 310 to 690° C., more preferably 320 to 680° C., and even more preferably 330 to 670° C., for example. Here, from the viewpoint of being able to lower the temperature during bonding, the softening point Ts of the glass adhesive layer 3 is preferably 690° C. or less, more preferably 680° C. or less, and even more preferably 670° C. or less. In addition, from the viewpoint of remelting, the softening point Ts of the glass adhesive layer 3 is preferably 310° C. or more, more preferably 320° C. or more, and even more preferably 330° C. or more.

[0111] It should be noted that the softening point Ts of the glass adhesive layer is the temperature at the fourth inflection point of the DTA curve of the glass alone.

[0112] The glass adhesive layer 3 preferably includes bismuth-based glass, vanadium-based glass, or borosilicate-based glass.

[0113] Bismuth-based glass refers to glass containing bismuth oxide (Bi2O3). The inclusion of bismuth oxide lowers the softening point Ts of the glass.

[0114] In addition to Bi2O3, bismuth-based glass may also contain B2O3, CeO2, SiO2, RO, R'2O, R"2O3, R"'O2, etc.

[0115] Vanadium-based glass refers to glass containing vanadium oxide (V2O5). The inclusion of vanadium lowers the softening point Ts of the glass.

[0116] In addition to V2O5, vanadium-based glass may also contain TeO2, B2O3, CeO2, SiO2, RO, R'2O, R"2O3, R"'O2, etc.

[0117] Borosilicate glass is borosilicate glass containing boron oxide (B2O3) and silicate (SiO2). When the content of silicate (SiO2) is low, the softening point Ts decreases.

[0118] Borosilicate glass may contain ZnO, RO, R'2O, R"2O3, R"'O2, etc. in addition to B2O3 and silicate SiO2.

[0119] By using the above-mentioned glass for the glass adhesive layer, when bonding the sheet glass 1 and the outer frame 2, it is not necessary to apply a voltage as in anodic bonding, and the sheet glass 1 and the outer frame 2 can be bonded simply by overlapping and heating them. Therefore, the manufacturing process is also simplified.

[0120] The thickness of the glass adhesive layer 3 is preferably 10 to 30 μm, more preferably 11 to 25 μm, and further preferably 12 to 20 μm. Here, from the viewpoint of filling the unevenness of the surface of the glass ceramic as the outer frame 2 bonded to the flat glass 1 to obtain good adhesion, the thickness of the glass adhesive layer 3 is preferably 10 μm or more, more preferably 11 μm or more, and further preferably 12 μm or more. In addition, if the glass adhesive layer 3 is too thick, its formation process will be complicated. In addition, from the viewpoint of suppressing the generation of cracks caused by expansion mismatch, the thickness of the glass adhesive layer 3 is preferably 30 μm or less, more preferably 25 μm or less, and further preferably 20 μm or less.

[0121] Other Compositions

[0122] like Figure 3 As shown, the cover glass 10 with a frame according to the present embodiment preferably further includes a sealing material layer 4 on the surface of the frame 2 located on the side opposite to the plate-shaped glass 1 side.

[0123] The sealing material layer 4 may be a layer composed of a metal film or a layer composed of glass frit.

[0124] When the sealing material layer 4 is composed of a metal film, the substrate and the framed cover glass 10 can be hermetically sealed by sealing using a metal ring such as a gold tin ring.

[0125] From the viewpoint of sealing performance when using a metal ring, the metal film preferably has a layer (not shown) containing one or more metal films selected from Au, Ag, Cu and Au-Sn alloy on its outermost surface, and more preferably has an Ag layer or an Au layer on the outermost surface. As a base of the above-mentioned film, it may further have a film (not shown) of Ni, Ti, Pd, Pt, Cu, etc.

[0126] In addition, when the outer frame 2 includes a metal conductor 6 described later, the metal film preferably has a metal coating obtained by using the same metal as the metal conductor 6 .

[0127] When the sealing material layer 3 is composed of glass frit, the substrate and the framed cover glass 10 can be hermetically sealed by sealing by heating.

[0128] Glass frit is a sealing glass composed of low melting point glass, and conventionally known glass frit can be used. For example, it is preferred to use low melting point glass such as tin-phosphate glass, bismuth glass, vanadium glass, lead glass, zinc borate alkali glass, etc. Among them, considering the reliability such as adhesion, adhesion reliability, airtight sealing, and the impact on the environment and human body, low melting point glass composed of tin-phosphate glass, bismuth glass, and vanadium glass is more preferred. The glass frit may further contain inorganic filling materials such as electromagnetic wave absorbers and low thermal expansion fillers.

[0129] The framed cover glass 10 of this embodiment preferably has a system capable of detecting cracks in the flat glass 1, depending on its application. As an example of the system, Figure 4 As shown, the conductive film 5 is preferably provided on the first main surface 1a of the sheet glass 1. In addition, the metal conductor 6 penetrating the frame 2 and provided perpendicularly to the sheet glass 1 is preferably provided inside the frame 2, and the conductive film 5 and the metal conductor 6 are preferably electrically connected.

[0130] The outer frame 2 is bonded to the first main surface 1a of the flat glass 1 via the glass adhesive layer 3. Figure 4 As shown in FIG. 1 , when the conductive film 5 is formed on all regions of the first main surface 1a of the flat glass 1, that is, also formed on the region joined to the outer frame 2, the flat glass 1 and the outer frame 2 are joined via the conductive film 5 in addition to the glass adhesive layer 3. In this case, the conductive film 5 made of an inorganic material is considered to be integrated with the flat glass 1, and is one mode of joining the flat glass 1 and the outer frame 2 via the glass adhesive layer 3.

[0131] The conductive film 5 can be made of conventionally known inorganic materials, and is preferably a transparent conductive film from the viewpoint of light transmittance, such as ITO (Indium Tin Oxide) film, SnO2 film, ZnO film, etc. Among them, an ITO film is preferred from the viewpoint of durability and resistance.

[0132] The thickness of the conductive film 5 is not particularly limited, but is preferably 0.05 to 1 μm, more preferably 0.1 to 0.8 μm, and further preferably 0.2 to 0.7 μm. Here, from the viewpoint of ensuring stable conductivity, the thickness of the conductive film 5 is preferably 0.05 μm or more, more preferably 0.1 μm or more, and further preferably 0.2 μm or more. In addition, from the viewpoint of maintaining permeability, the thickness of the conductive film 5 is preferably 1 μm or less, more preferably 0.8 μm or less, and further preferably 0.7 μm or less.

[0133] The conductive film 5 only needs to be formed on at least a portion of the first main surface 1a of the flat glass 1. If the purpose of detecting cracks in the flat glass 1 is considered, it is preferably formed at least in an effective area, that is, an area irradiated with light from a light source, and more preferably formed in the entire area of ​​the first main surface 1a of the flat glass 1.

[0134] When films or layers other than the conductive film 5 are formed on the first main surface 1 a of the sheet glass 1 , the conductive film 5 is preferably formed outside these other films or layers, that is, on the outermost surface where the substrate having the light emitting element or the light receiving element is located.

[0135] The metal conductor 6 is sometimes called a through hole, and is a conductor that electrically connects the upper wiring to the lower wiring. In this embodiment, the metal conductor 6 is connected to the conductive film 5 to connect the conductive film 5 to a detector for detecting cracks in the flat glass 1.

[0136] The metal conductor 6 can be made of a conventionally known material by a conventionally known method. For example, before or after the glass ceramic constituting the outer frame 2 is fired, a hole penetrating the inner portion of the outer frame 2 is provided, and the metal conductor 6 is laid in the hole.

[0137] The metal conductor 6 may be any metal having conductivity, and is preferably one or more metals selected from Ag, Au, and Cu, and more preferably Ag, from the viewpoint of ease of manufacture. Ease of manufacture means that the glass ceramic forming the outer frame 2 can be sintered together when being fired.

[0138] The shape of the metal conductor 6 is not particularly limited, but a metal wire is preferred from the viewpoint of making it easy to penetrate the inside of the outer frame 2. The diameter of the metal wire, i.e., the diameter of the through hole, is preferably 0.05 to 0.2 mm, and more preferably 0.05 to 0.1 mm. Here, from the viewpoint of preventing the unevenness of the metal conductor 6 from becoming larger and the glass ceramics serving as the outer frame 2 from cracking during calcination, the through hole diameter is more preferably 0.2 mm or less, and further preferably 0.1 mm or less. In addition, the lower limit of the through hole diameter is not particularly limited, but from the viewpoint of preventing the metal conductor 6 from breaking, it is preferably 0.05 mm or more.

[0139] like Figure 5 As shown in (a) of FIG. 1 , the framed cover glass 10 of the present embodiment may further include an antireflection film 7 or the like on at least one of the first principal surface 1 a and the second principal surface 1 b of the plate-shaped glass 1 .

[0140] The anti-reflection film 7 is preferably formed on at least one main surface of the flat glass 1. That is, the anti-reflection film 7 may be formed on the first main surface 1a on the side where the substrate having the light emitting element or the light receiving element is located, or may be formed on the second main surface 1b on the other side. Figure 5 As shown in (a) in FIG. 1 , it can also be formed on both main surfaces.

[0141] When the flat glass 1 includes the light diffusion portion 1c, it is preferable that Figure 5 As shown in (b) in FIG. 1 , an antireflection film 7 is formed on the surface of the light diffusion portion 1 c , that is, on the outer side of the light diffusion portion 1 c .

[0142] The anti-reflection film 7 is not particularly limited as long as it has at least an anti-reflection function of reducing the reflectivity of light of the design wavelength. From the viewpoint of preventing the anti-reflection film 7 from disappearing when the outer frame 2 is calcined, the anti-reflection film 7 is preferably a film formed of an inorganic material, for example, a thin film with a single-layer structure, a dielectric multilayer film having two or more dielectric layers with different refractive indices such as SiO2 and Ta2O5, etc., can be cited.

[0143] The sheet glass 1 may further include a layer, a film, etc. having some function in addition to the above within a range not impairing the effects of the present invention.

[0144] In addition, when the flat glass 1 has a film formed of an inorganic material such as the antireflection film 7 and the conductive film 5, when these films are formed to the bonding region with the outer frame 2, the flat glass 1 and the outer frame 2 are bonded via the above-mentioned films. In this case, it is also judged that the film is integrated with the flat glass 1, and the flat glass 1 and the outer frame 2 are bonded via the glass adhesive layer 3.

[0145] The framed cover glass 10 can be arbitrarily deformed within a range that does not impair the effects of the present invention. For example, by cutting off a portion of the frame 2 and chamfering the corners to form a straight line passing through the flat glass 1 and the frame 2, the metal conductor 6 can be removed.

[0146] <Semiconductor light-emitting device, semiconductor light-receiving device>

[0147] The semiconductor light emitting device of this embodiment includes a cover glass with a frame, a substrate, and a light emitting element provided on the substrate.

[0148] The cover glass with a frame can be the cover glass with a frame described in the above-mentioned <Cover glass with a frame>, and the preferred embodiment is the same. It is particularly preferred that the surface of the frame located on the side opposite to the flat glass side has a sealing material layer composed of a metal film or glass frit, and more preferably has a sealing material layer composed of a metal film. The metal film preferably has an Ag layer or an Au layer on its outermost surface, and the cover glass with a frame is preferably integrated with the substrate via a gold tin ring to airtightly seal the light-emitting element.

[0149] The semiconductor light receiving device of this embodiment includes a cover glass with a frame, a substrate, and a light receiving element provided on the substrate.

[0150] The cover glass with a frame may be the cover glass with a frame described in the above-mentioned <Cover glass with a frame>, and the preferred embodiment is the same. It is particularly preferred that the surface of the frame located on the side opposite to the flat glass side has a sealing material layer composed of a metal film or glass frit, and more preferably has a sealing material layer composed of a metal film. The metal film preferably has an Ag layer or an Au layer on its outermost surface, and the cover glass with a frame is preferably integrated with the substrate via a gold tin ring to airtightly seal the light receiving element.

[0151] In semiconductor light-emitting devices and semiconductor light-receiving devices, the cover glass 10 with a frame of the present embodiment can ensure verticality even if the height of the frame is above a certain level, and can also have tightness with the cover glass. In addition, damage and cracks on the surface of the flat glass are reduced, and the resistance to chemical liquid is also high. For these reasons, the cover glass 10 with a frame of the present embodiment is suitable for airtight sealing of the substrate in the semiconductor light-emitting device and the substrate in the semiconductor light-receiving device.

[0152] As the light emitting element, for example, a light emitting diode (LED), a semiconductor laser (LD), etc. can be cited. As the substrate in this case, there is no particular limitation as long as it is insulating, and a ceramic substrate is preferably used from the viewpoint of heat dissipation. For example, the ceramic substrate is preferably an aluminum nitride (AlN) substrate, an aluminum oxide (Al2O3) substrate, or a low temperature co-fired ceramic (LTCC; Low Temperature Co-fired Ceramics) substrate.

[0153] Examples of semiconductor light-emitting devices having these include backlights of mobile phones and LCD televisions, light-emitting parts of operating buttons of small information terminals, deep ultraviolet LEDs for automotive or decorative lighting, sterilization purposes, laser parts of 3D ranging sensors, and other light sources.

[0154] Examples of the light receiving element include a MEMS sensor, etc. As the substrate in this case, a silicon substrate is preferable.

[0155] <Method for manufacturing cover glass with frame>

[0156] One embodiment of a method for manufacturing the framed cover glass 10 will be described.

[0157] The manufacturing method of the glass ceramic as the outer frame 2 in the cover glass 10 with an outer frame is not particularly limited, and it can be obtained, for example, by molding a mixture of borosilicate glass powder and filler as a glass matrix, that is, a precursor of the glass ceramic, and calcining and sintering it. Specifically, there can be mentioned a method of molding the above-mentioned precursor into a sheet called a green sheet and calcining it.

[0158] An example of a method for producing a green sheet is shown below.

[0159] First, a raw material mixture obtained by mixing and blending each raw material in a desired glass composition is melted, cooled, and crushed to obtain glass powder. The glass powder obtained by crushing is calcined to form a glass matrix to determine the glass composition of the glass ceramic. Therefore, the powder of the borosilicate glass in this embodiment contains boron oxide and silicate, and also contains aluminum oxide. The preferred embodiment of the glass powder is the same as the preferred embodiment described for the glass matrix in the above-mentioned <Cover glass with outer frame>.

[0160] The melting temperature of the raw material mixture is preferably, for example, 500 to 800° C. or higher, and the melting time is preferably, for example, 30 to 60 minutes.

[0161] The pulverization may be performed by dry pulverization or wet pulverization. In the case of wet pulverization, water, ethanol, etc. may be used as a solvent.

[0162] For the pulverization, for example, a pulverizer such as a roll mill, a ball mill, or a jet mill can be used.

[0163] The 50% particle size (D 50 ) is preferably 0.5 to 10 μm, more preferably 1 to 9 μm. Here, from the viewpoint of preventing the glass powder from agglomerating and becoming difficult to handle, and also preventing the time required for powderization from being prolonged, the 50% particle size (D 50 ) is preferably 0.5 μm or more, more preferably 1 μm or more. In addition, from the viewpoint of preventing the glass softening point Ts from rising and insufficient sintering, the 50% particle size (D 50 ) is preferably 10 μm or less, more preferably 9 μm or less.

[0164] From the viewpoint of obtaining good sinterability and preventing a decrease in reflectivity due to undissolved components remaining in the sintered body, the maximum particle size of the glass powder is preferably 20 μm or less, more preferably 10 μm or less.

[0165] The particle size can be adjusted by classifying the pulverized particles as required.

[0166] Next, the glass powder and the filler are mixed to obtain a glass ceramic precursor.

[0167] The filler may contain aluminum oxide, and the same fillers as those described in the above-mentioned <Cover glass with frame> may be used, and the preferred embodiments are also the same.

[0168] The fillers are mixed so that the total volume fraction in the obtained glass ceramic is 40 to 65%. In addition, the fillers are mixed so that the volume fraction of alumina contained in the fillers in the glass ceramic is 10 to 65%.

[0169] An organic solvent, a plasticizer, a binder, a dispersant, and the like are mixed with a glass ceramic precursor as necessary to prepare a slurry or a paste.

[0170] Examples of the organic solvent include alcohols, ketones, and aromatic hydrocarbons. More specifically, toluene, methyl ethyl ketone, methanol, 2-butanol, xylene, and the like can be used, and these can be used alone or in combination of two or more.

[0171] Examples of the plasticizer include adipic acid-based plasticizers and phthalic acid-based plasticizers. More specifically, bis(2-ethylhexyl) adipate, dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and the like can be used.

[0172] Examples of the binder include thermally decomposable resins, and more specifically, acrylic resins, polyvinyl butyral, and the like can be used.

[0173] Examples of the dispersant include surfactant-type dispersants, and more specifically, DISPERBYK 180 (trade name, manufactured by BYK-Chemie) and the like can be used.

[0174] The sheet obtained by casting the obtained slurry or paste is called a green sheet. Specifically, for example, the green sheet is obtained by applying the slurry or paste on a film and drying it.

[0175] The thickness of the green sheet is not particularly limited and can be adjusted according to the thickness during coating, slurry concentration, and the like.

[0176] Next, a method of forming the outer frame 2 from the green sheet obtained above and a method of bonding the outer frame 2 to the plate-shaped glass 1 will be described.

[0177] First, an appropriate number of green sheets are stacked according to the desired height of the outer frame 2. Then, the inner part is punched out by a puncher to form the outer frame shape. At this time, when the cover glass 10 with the outer frame has a metal conductor 6, a through hole for penetrating the metal conductor 6 can also be formed. It should be noted that when forming glass ceramics, it is also possible to use a molded body formed by molding a precursor of glass ceramics using a mold or the like instead of the above-mentioned green sheets. From the perspective of making it easy to pass wiring through each layer, green sheets are preferred.

[0178] Green sheets can be produced one by one according to a desired outer frame shape, or a larger green sheet can be produced and punched out at multiple locations using a puncher to produce an outer frame of a multi-piece connected substrate in which multiple sheets are connected.

[0179] After the stacked body of green sheets is fired separately to prepare glass ceramics in advance, it is bonded to a flat glass through a glass adhesive layer.

[0180] Among them, it is preferable to laminate green sheets, punch out to form a multi-sheet connected substrate, and then sinter it to form a multi-sheet outer frame, and bond the flat glass thereto via a glass adhesive layer.

[0181] The stack of green sheets is degreased as necessary and further sintered, whereby the stack of green sheets becomes glass ceramics in which a filler is dispersed in a glass matrix, thereby obtaining the outer frame 2 .

[0182] The green sheet may be defatted as required, and is preferably, for example, at 350 to 550° C. The defatting time is, for example, preferably 1 to 10 hours.

[0183] The temperature during firing of the green sheet is a temperature equal to or higher than the glass softening point Ts of the glass matrix in the glass ceramic.

[0184] The specific calcination temperature varies depending on the glass composition in the glass ceramic, and is preferably 750 to 1000° C., more preferably 775 to 950° C., and even more preferably 800 to 900° C. Here, from the viewpoint of obtaining sufficient sinterability, the calcination temperature is preferably 750° C. or higher, more preferably 775° C. or higher, and even more preferably 800° C. or higher. In addition, from the viewpoint of preventing the melting of the metal constituting the sealing material layer 4, the metal conductor 6, etc., the calcination temperature is preferably 1000° C. or lower, more preferably 950° C. or lower, and even more preferably 900° C. or lower.

[0185] The calcination time of the green sheet is preferably 10 to 120 minutes, more preferably 15 to 90 minutes, and further preferably 25 to 60 minutes. Here, from the viewpoint of obtaining sufficient sinterability, the calcination time is preferably 10 minutes or more, more preferably 15 minutes or more, and further preferably 25 minutes or more. In addition, from the viewpoint of productivity, the calcination time is preferably 120 minutes or less, more preferably 90 minutes or less, and further preferably 60 minutes or less.

[0186] The shape of the outer frame 2 is determined by the shape of the green sheet. That is, the shape of the green sheet when punched becomes the source of the shape of the inner side of the outer frame 2. In addition, the outer shape of the green sheet becomes the source of the shape of the outer side of the outer frame 2. In the case of obtaining the cover glass 10 with an outer frame by dividing it from a multi-piece connected substrate, the shape when divided after calcination becomes the shape of the outer side of the outer frame 2.

[0187] The flat glass 1 can be produced by a conventionally known method, or a commercially available product can be used.

[0188] For example, glass raw materials are blended in such a manner as to obtain glass of a desired composition, and heated and melted. Then, the molten glass is homogenized by bubbling, stirring, adding a clarifier, etc., and formed into a glass plate of a predetermined thickness by a known forming method, and then slowly cooled. After the molten glass is homogenized, it can be formed into a block, slowly cooled, and then cut to form a flat plate.

[0189] Examples of the method for forming a flat glass include a float method, a press method, a melt method, and a down-draw method. From the viewpoint of controlling the thickness of the glass, the down-draw method is particularly preferred.

[0190] When the conductive film 5 is formed on the main surface of the sheet glass 1 and is electrically connected to the metal conductor 6 , it is preferable to form the conductive film 5 before the outer frame 2 and the sheet glass 1 are stacked with the glass adhesive layer 3 interposed therebetween.

[0191] The conductive film 5 can be formed by a conventionally known method on the first main surface 1a of the flat glass 1. For example, when the conductive film is an ITO film, it is preferably formed by a sputtering method.

[0192] When the light diffusion portion 1 c and the antireflection film 7 are provided on the same first main surface 1 a of the sheet glass 1 , the conductive film 5 is preferably formed on the outermost surface thereof, that is, on the side closest to the substrate.

[0193] When the light diffusion portion 1c is directly processed on the main surface of the flat glass 1 and the anti-reflection film 7 is formed, the above processing and film formation can be performed before the outer frame 2 is overlapped with the flat glass 1 via the glass adhesive layer 3, or after the cover glass 10 with the outer frame is obtained. However, when the light diffusion portion 1c is provided and the conductive film 5 is provided as described above, it is preferred to perform the processing of the light diffusion portion 1c and the formation of the conductive film 5 before overlapping the outer frame 2 and the flat glass 1 via the glass adhesive layer 3.

[0194] The antireflection film 7 can be formed by a conventionally known method, for example, by sequentially laminating a high refractive index layer and a low refractive index layer on the main surface of the flat glass 1 using a known film forming method such as sputtering or vapor deposition.

[0195] When the antireflection film 7 is formed on the second main surface 1 b which is the main surface opposite to the side joined to the frame 2 of the plate glass 1 , it can be formed after the cover glass 10 with the frame is obtained.

[0196] The softening point Ts of the glass adhesive layer 3 is preferably lower than the softening point Ts of borosilicate glass and lower than the glass transition temperature Tg of the sheet glass. This allows the sheet glass 1 and the outer frame 2 to be bonded at a relatively low temperature without causing damage or cracks to the sheet glass 1 and the outer frame 2.

[0197] The temperature during bonding is, for example, preferably 330 to 700° C., more preferably 350 to 690° C. The time during bonding is, for example, preferably 10 to 60 minutes.

[0198] Examples of glass having a softening point Ts lower than the softening point Ts of borosilicate glass and lower than the glass transition temperature Tg of flat glass include bismuth-based glass, vanadium-based glass, and borosilicate glass.

[0199] In order to make the thickness of the glass adhesive layer 3 10 μm or more, a method of using a screen with a large mesh size, a method of printing multiple times, and the like are exemplified.

[0200] In addition, the glass adhesive layer 3 can be thickened by printing the glass frit to be the glass adhesive layer 3 on both the first main surface 1 a of the flat glass 1 and the surface of the outer frame 2 .

[0201] From the viewpoint of suppressing the complication of the process and cracking due to expansion mismatch, the thickness of the glass adhesive layer 3 is preferably 30 μm or less.

[0202] When the cover glass with a frame is a multi-piece connection substrate, individual cover glasses with a frame 10 are obtained by cutting between adjacent holes using a cutter or a laser.

[0203] From the perspective of adhesion, it is preferred that both surfaces of the glass ceramic, i.e., the surface in contact with the glass adhesive layer and the surface opposite to the surface, be smoothed by grinding or the like before firing to bond the outer frame to the flat glass via the glass adhesive layer.

[0204] Specifically, it is preferred that the sealing property of the sealing material layer is improved by smoothing the maximum height roughness Rz of the surface on the side opposite to the side in contact with the glass bonding layer. The above-mentioned maximum height roughness Rz is preferably 5 μm or less, more preferably 4.5 μm or less, and further preferably 4 μm or less. The maximum height roughness Rz of the glass ceramic obtained by calcining the precursor of the glass ceramic is usually about 10 μm, and the above-mentioned maximum height roughness Rz can be reduced to 5 μm or less by performing a flattening process such as grinding.

[0205] The sealing material layer 4 is formed after both surfaces of the outer frame 2 which is fired to become glass ceramic are subjected to a planarization process such as polishing.

[0206] The sealing material layer 4 is formed of a metal film or glass frit, and can be formed by a conventionally known method. For example, when the sealing material layer 4 is a metal film, it can be formed by applying a conductive paste made by adding a carrier such as ethyl cellulose to metal powder and a solvent as required, etc., using a screen printing method. In addition, when the sealing material layer 4 is a glass frit, it can be formed by applying a paste made by mixing a glass frit of a low melting point glass with a carrier that dissolves a resin as a binder component in a solvent.

[0207] When a film serving as a base is formed on the surface of the metal film of the sealing material layer 4 or between the outer frame and the metal film, the film may be formed by a conventionally known method, such as electroplating, electroless plating, sputtering, or vapor deposition.

[0208] When providing the metal conductor 6, for example, metal paste can be filled into the preformed through-holes by screen printing. The metal conductor 6 can be filled into the through-holes of the green sheet formed into the outer frame shape, or can be filled into the through-holes of the outer frame formed by firing the glass ceramic.

[0209] As mentioned above, the cover glass with a frame etc. of this embodiment are described in detail, and another aspect of this embodiment is as follows.

[0210] [1] A cover glass with a frame, comprising: a sheet of glass having a first main surface and a second main surface facing each other; and a frame bonded to the first main surface of the sheet of glass via a glass adhesive layer;

[0211] The outer frame is made of glass ceramics in which fillers are dispersed in borosilicate glass.

[0212] The borosilicate glass and the filler both contain aluminum oxide.

[0213] The volume fraction of the filler in the glass ceramic is 40 to 65%.

[0214] The volume fraction of the aluminum oxide contained in the filler in the glass ceramic is 10 to 65%.

[0215] The absolute value of the difference between the average thermal expansion coefficient of the plate glass and the outer frame at 50 to 350°C is 20×10 -7 / ℃ below.

[0216] [2] The cover glass with a frame according to [1] above, wherein a maximum height roughness Rz of a surface of the frame located on the side opposite to the flat glass side is 5 μm or less.

[0217] [3] The cover glass with a frame according to [1] or [2], wherein the softening point Ts of the glass adhesive layer is lower than the softening point Ts of the borosilicate glass,

[0218] The softening point Ts of the glass adhesive layer is lower than the glass transition temperature Tg of the plate glass.

[0219] [4] The cover glass with a frame according to [3] above, wherein the glass adhesive layer comprises bismuth-based glass, vanadium-based glass, or borosilicate-based glass,

[0220] The glass adhesive layer has a thickness of 10 to 30 μm.

[0221] [5] The cover glass with a frame according to any one of [1] to [4] above, wherein the height of the frame is 350 μm to 4 mm.

[0222] [6] The framed cover glass according to any one of [1] to [5], wherein the flat glass has a light diffusion portion on the first main surface.

[0223] The light diffusion portion is formed by directly processing the plate-shaped glass.

[0224] [7] The cover glass with a frame according to [6] above, wherein the light diffusion portion is formed inside a region to which the frame is bonded.

[0225] [8] The framed cover glass according to any one of [1] to [7], wherein the flat glass has a conductive film on the first main surface.

[0226] A metal conductor is provided inside the outer frame, penetrating the outer frame and arranged perpendicularly to the flat glass.

[0227] The conductive film is electrically connected to the metal conductor.

[0228] [9] The cover glass with a frame according to any one of [1] to [8], wherein the frame further comprises a sealing material layer on a surface on the side opposite to the flat glass side.

[0229] The sealing material layer is made of a metal film or glass frit.

[0230]

[10] The cover glass with a frame according to [9] above, wherein the sealing material layer is composed of a metal film,

[0231] The metal film has an Ag layer or an Au layer on its outermost surface.

[0232]

[11] A semiconductor light emitting device comprising: the cover glass with a frame as described in

[10] above, a substrate, and a light emitting element provided on the substrate,

[0233] The cover glass with a frame is integrated with the substrate via the sealing material layer and the gold tin ring in the cover glass with a frame, so that the light emitting element is hermetically sealed.

[0234]

[12] A semiconductor light receiving device comprising: the cover glass with a frame as described in

[10] above, a substrate, and a light receiving element provided on the substrate.

[0235] The cover glass with a frame is integrated with the substrate via the sealing material layer and the gold tin ring in the cover glass with a frame, and the light receiving element is hermetically sealed.

[0236] Example

[0237] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited thereto.

[0238] Examples 1-2, 1-4 and 1-6 are examples, and Examples 1-1, 1-3, 1-5 and 1-7 to 1-10 are comparative examples. Examples 2-2 to 2-4 are examples, and Comparative Example 2-1 is a comparative example. Examples 3-1, 3-2 and 3-5 are examples, and Examples 3-3 and 3-4 are comparative examples. Example 4-1 is an example, and Example 4-2 is a reference example.

[0239] It should be noted that Examples 1-1 to 1-10 and Examples 2-1 to 2-4 are merely glass ceramics used as outer frames, and are not cover glasses with outer frames in which an outer frame made of glass ceramics is bonded to a flat glass plate. However, the shape retention, sintering properties, and chemical liquid resistance of the outer frames can be considered to be equivalent to those of cover glasses with outer frames, and are therefore considered to be embodiments or comparative examples.

[0240] Although Examples 4-1 and 4-2 do not include a light emitting element or a light receiving element, the sealing performance between the substrate and the cover glass with a frame can be considered to be equivalent to that of a semiconductor light emitting and receiving device including a light emitting element or a light receiving element, and thus are considered as Examples or Comparative Examples.

[0241] [Outer frame: Example 1-1 to Example 1-10]

[0242] The fillers listed in Table 1 were mixed in borosilicate glass (manufactured by AGC, trade name ASF-1860) containing 10 wt% of aluminum oxide in the manner of the volume fractions listed in Table 1 to obtain a precursor of glass ceramics. It should be noted that cordierite refers to a ceramic composed of three components, 2MgO·2Al2O3·5SiO2, and contains aluminum oxide. In addition, forsterite refers to a ceramic composed of two components, 2MgO·SiO2, and does not contain aluminum oxide.

[0243] The glass ceramic precursor obtained above was pressed into a cylindrical powder compact having a diameter of 17 mm and a height of 5 mm, and the pressed powder compact was calcined at 850° C. to obtain glass ceramic.

[0244] In Table 1, “filler volume fraction” refers to the volume fraction of the filler in the glass ceramic, and “alumina volume fraction” refers to the volume fraction of alumina contained in the filler in the glass ceramic.

[0245] [Table 1]

[0246] Table 1

[0247]

[0248] The obtained glass ceramics were evaluated for shape retainability and sinterability.

[0249] Specifically, the shape retainability was determined using a stereoscopic microscope MVX10 manufactured by EVIDENT.

[0250] The results are shown in the "Shape Retention" of Table 1, and "○" indicates that the glass ceramic has high verticality and excellent shape retention. Specifically, since the glass ceramic is formed by calcining a cylindrical powder compact, the glass ceramic also becomes a cylindrical shape similar to the powder compact. However, it is difficult to become a completely similar shape as it is calcined. Therefore, the longest length in the transverse direction of the cross section of the cylindrical glass ceramic, that is, the direction corresponding to the diameter 2r of the circle forming the upper surface and bottom surface of the cylinder, is set to L1, and the transverse direction of the area where the glass ceramic is joined to the flat glass, that is, the diameter of the circle in the bottom surface of the cylinder is set to L2, and the case where the difference represented by (L1-L2) is less than 1.0 mm is evaluated as good and recorded as "○".

[0251] In Table 1, "×" for "Shape Retention" means that the difference represented by (L1-L2) is larger than 1.0 mm, which means that the verticality of the glass ceramic is broken and the glass ceramic is curved in the lateral direction, which is poor.

[0252] The sinterability was evaluated using a stereoscopic microscope MVX10 manufactured by EVIDENT.

[0253] The results are shown in the "Sintering Property" of Table 1. "○" indicates that no pores larger than 1 mm are observed when the surface of the glass ceramic is observed under a microscope, which is good. "×" indicates that pores larger than 1 mm are observed and the sintering properties of the glass component and filler in the glass ceramic are insufficient, which is poor.

[0254] According to the above results, it can be known that by satisfying the volume fraction of the filler in the glass ceramic of 40 to 65% and the volume fraction of the aluminum oxide contained in the filler in the glass ceramic of 10 to 65%, it is possible to have both shape retention and sinterability, which were previously difficult to achieve. Since the shape retention is good, the verticality of the outer frame can be achieved. In addition, since the wettability of the filler and the borosilicate glass is improved, the sinterability of the glass ceramic is improved, so a highly airtight outer frame can be formed.

[0255] [Outer frame: Example 2-1]

[0256] The fillers listed in Table 2 were mixed with bismuth-based glass (ASF-4001B manufactured by AGC Corporation) at the volume fractions listed in Table 2 to obtain a powder as a precursor of glass ceramics.

[0257] A mixture of toluene:methyl ethyl ketone:methanol:2-butanol=3:3:1:1 (mass ratio) as an organic solvent, bis(2-ethylhexyl) adipate as a plasticizer, an acrylic resin as a binder and a dispersant (manufactured by BYK-Chemie, trade name: DISPERBYK180) are added to a glass ceramic precursor and mixed to prepare a slurry.

[0258] The slurry was applied onto a polyethylene terephthalate (PET) film by a doctor blade method and dried to produce a green sheet having a thickness of 200 μm.

[0259] Six of the green sheets obtained above were stacked, cut into a 45 mm square sheet stack, and calcined at the calcination temperature described in 2.

[0260] In Table 2, “filler volume fraction” refers to the volume fraction of the filler in the glass ceramic, and “alumina volume fraction” refers to the volume fraction of alumina contained in the filler in the glass ceramic.

[0261] [Outer frame: Example 2-2 to Example 2-4]

[0262] The fillers listed in Table 2 were mixed with borosilicate glass (manufactured by AGC Corporation, trade name ASF-1860) containing 10 wt % of aluminum oxide at the volume fractions listed in Table 2 to obtain a powder as a precursor of glass ceramics.

[0263] A mixture of toluene:methyl ethyl ketone:methanol:2-butanol=4:4:1:1 (mass ratio) as an organic solvent, bis(2-ethylhexyl) adipate as a plasticizer, butyraldehyde ester as a binder and a dispersant (manufactured by BYK-Chemie, trade name: DISPERBYK180) are added to a glass ceramic precursor and mixed to prepare a slurry.

[0264] The slurry was applied onto a polyethylene terephthalate (PET) film by a doctor blade method and dried to produce a green sheet having a thickness of 200 μm.

[0265] Six of the green sheets obtained above were stacked, cut into a 45 mm square sheet stack, and calcined at the calcination temperature described in 2.

[0266] [Table 2]

[0267] Table 2

[0268]

[0269] The chemical resistance of the obtained glass-ceramics was evaluated.

[0270] Specifically, as an acid resistance test, the glass ceramic was immersed in a 10% sulfuric acid aqueous solution at 25° C. for 2 hours. The presence of corrosion after immersion was visually confirmed, and the weight loss rate was calculated from the weight change before and after immersion in the 10% sulfuric acid aqueous solution.

[0271] The results are shown in Table 2, "Drug solution resistance".

[0272] From the above results, it can be seen that Examples 2-2 to 2-4 using borosilicate glass as a glass substrate showed neither corrosion caused by a 10% sulfuric acid aqueous solution nor weight loss, and therefore had better chemical resistance than glass ceramics using conventional bismuth glass as a glass substrate. Therefore, it is suggested that the chemical resistance is high for metallization treatment or mounting in semiconductor light emitting devices, semiconductor light receiving devices, etc.

[0273] [Cover glass with frame: Example 3-1 to Example 3-5]

[0274] Cordierite as a filler was mixed into borosilicate glass containing 10 wt% of alumina (manufactured by AGC, trade name ASF-1860) so that the volume fraction of the filler in the glass ceramic was 51% and the volume fraction of the alumina contained in the filler in the glass ceramic was 12%, thereby obtaining a powder as a precursor of the glass ceramic.

[0275] A mixture of toluene:methyl ethyl ketone:methanol:2-butanol=4:4:1:1 (mass ratio) as an organic solvent, bis(2-ethylhexyl) adipate as a plasticizer, butyraldehyde ester as a binder and a dispersant (manufactured by BYK-Chemie, trade name: DISPERBYK180) are added to a glass ceramic precursor and mixed to prepare a slurry.

[0276] The slurry was applied onto a polyethylene terephthalate (PET) film by a doctor blade method and dried to produce a green sheet.

[0277] Six green sheets obtained above were stacked, and a puncher was used to obtain a panel having a multi-piece frame shape in which 64 unsintered green sheets were connected and had 8×8 square holes of 4.0 mm×4.0 mm.

[0278] The above panel was fired at 850° C. to obtain a multi-piece outer frame made of glass ceramics having a thickness of about 1 mm and having 8×8 square holes of 3.4 mm×3.4 mm.

[0279] Next, both the main surface on the flat glass side of the outer frame and the main surface opposite thereto were polished so that the maximum height roughness Rz was 3 μm.

[0280] In Examples 3-1 and 3-5, vanadium glass (AGC, TNS062-ZC2-P150) was used as a glass paste in a frame shape around an opening of glass ceramics using a screen printer. In Examples 3-2, 3-3, and 3-4, bismuth glass (AGC, AP4115AB) was used as a glass paste in a frame shape around an opening of glass ceramics using a screen printer. Screen printing used a screen with a mesh size of 325 and an emulsion thickness of 10 μm. Then, the paste was dried at 120°C for 10 minutes and pre-calcined at the calcination temperature described in Table 3 for 10 minutes.

[0281] On the other hand, as flat glass, a glass plate made of alkali-free borosilicate glass (AGC, EN-A1) with a size of 50 mm × 50 mm and a thickness of 0.5 mm, a glass plate made of borosilicate glass (Schott, D263 (registered trademark) with a size of 50 mm × 50 mm and a thickness of 0.5 mm, and a glass plate made of borosilicate glass (Schott, TEMPAX (registered trademark) with a size of 50 mm × 50 mm and a thickness of 0.7 mm) were prepared. The average coefficient of thermal expansion of these flat glass plates is as described in "CTE" of Table 3.

[0282] The glass paste described in Table 3 was also printed on these flat glass sheets in the same pattern as above, and was pre-fired at the firing temperature described in Table 3 for 10 minutes.

[0283] Next, the plate-shaped glass and the glass ceramic were arranged so that the glass frit printed surfaces thereof faced each other, and the plate-shaped glass and the glass ceramic were calcined for 1 hour at the calcination temperature listed in Table 3 while the four corners were fixed with a clamp, so that the plate-shaped glass and the glass ceramic were bonded via the glass adhesive layer. Thus, a cover glass with an outer frame as a multi-piece connection substrate was obtained.

[0284] The thickness of the glass adhesive layer after bonding is shown in Table 3.

[0285]

[0286] The obtained cover glass with a frame as a multi-sheet connection substrate was evaluated for bonding properties between the flat glass and the frame.

[0287] Specifically, the cover glass with the outer frame was placed with the opening facing upward, and fluorescent ink was dropped thereon. The presence or absence of ink seeping into the joining portion between the flat glass and the outer frame was confirmed by microscopic observation.

[0288] The results are shown in "Joining" of Table 3, where a case where no bleeding of the fluorescent ink occurred is evaluated as good and indicated by "○", and a case where bleeding of the fluorescent ink was observed is evaluated as poor and indicated by "×".

[0289] In Table 3, the absolute value of the difference in average thermal expansion coefficient between the flat glass and the outer frame is represented by |ΔCTE|, where |ΔCTE| is 20×10 -7 / ℃ or less, all of Examples 3-1, 3-2, and 3-5 were confirmed to have good bonding properties. In addition, in Example 3-3, although bonding was achieved by making the thickness of the glass adhesive layer thicker to a certain extent compared to Example 3-4, cracks in the flat glass were observed, indicating that it was not suitable as a cover glass with a frame. Even when the thickness of the glass adhesive layer of Examples 3-1, 3-2, and 3-5 was set to 10μm or more, cracks in the flat glass did not occur in the cover glass with a frame, and the bonding properties were also good.

[0290] [Device: Example 4-1]

[0291] For the cover glass with outer frame as the multi-piece connection substrate obtained in Example 3-1 above, the opening is masked, and a metal layer of Ti0.1μm / Pt0.2μm / Au0.1μm is sequentially formed on the surface of the Ag layer as the sealing material layer by vapor deposition. That is, the outermost surface of the sealing material layer is the Au layer. Then, the cover glass with outer frame with the sealing material layer is cut into individual pieces by a dicing knife at the center line of the opening of 8×8 grids.

[0292] On the other hand, a 50 mm square AlN substrate was used as the substrate of the semiconductor light-receiving and light-emitting device, and a metal layer of Ti0.1 μm / Pt0.2 μm / Au0.1 μm was sequentially formed on one main surface thereof by vapor deposition. That is, the outermost surface of the metal layer was the Au layer. Then, the substrate was singulated into 5.0 mm square pieces by a dicing knife.

[0293] Then, the cover glass with the frame obtained above, the gold tin ring, and the AlN substrate obtained above were placed in order, and heated at 300° C. for 1 minute in a N 2 atmosphere so that the AlN substrate was in contact with a hot plate to produce a sealed sample.

[0294] It should be noted that during the above arrangement, the opening of the gold tin ring was aligned with the opening of the cover glass with a frame using a microscope. The gold tin ring had an outer diameter of 5 mm, an inner diameter of 3.4 mm, and a thickness of 20 μm.

[0295] [Device: Example 4-2]

[0296] A single-piece cover glass with a sealing material layer was obtained in the same manner except that the main surface on the flat glass side and the main surface opposite to the main surface of the glass ceramic of the cover glass with a frame obtained in Example 3-1 were not polished to a maximum height roughness Rz of 3 μm. The maximum height roughness Rz of both surfaces of the main surface was 10 μm.

[0297] Using this framed cover glass, a sealed sample was prepared in the same manner as in Example 4-1.

[0298] The sealing samples of Examples 4-1 and 4-2 were subjected to a gross leak test.

[0299] In the gross leakage test, after He was pressurized at 5 kN for 2 hours, the sealed sample was immersed in Fluorinert at 125° C. for 30 seconds, and the presence or absence of He bubbles was visually checked.

[0300] No gross leakage was observed in Example 4-1, but gross leakage was observed in Example 4-2. The results indicate that when the cover glass with a frame of the present embodiment is mounted on a light-receiving and light-emitting device, it is preferred that the surface of at least one side of the frame in contact with the sealing material layer be polished before forming the sealing material layer so that the maximum height roughness Rz is 5 μm or less.

[0301] It is considered that if the maximum height roughness Rz is larger than 5 μm, it is difficult to fill the unevenness on the main surface of the outer frame with the film thickness of the sealing material layer, resulting in a decrease in the airtight sealing layer.

[0302] Although the present invention has been described in detail with reference to specific embodiments, it is obvious to those skilled in the art that various changes and modifications may be added without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2022-122179) filed on July 29, 2022, and its contents are incorporated herein by reference.

[0303] Explanation of symbols

[0304] 1 Flat glass

[0305] 1a First main surface

[0306] 1b Second main surface

[0307] 1c Light diffusion part

[0308] 2. Frame

[0309] 3Glass bonding layer

[0310] 4 Sealing material layer

[0311] 5Conductive film

[0312] 6. Metal conductor

[0313] 7 Anti-reflective film

[0314] 10 Cover glass with frame

Claims

1. A cover glass with a frame, comprising: a flat glass having a first main surface and a second main surface facing each other, and a frame bonded to the first main surface of the flat glass via a glass adhesive layer, The outer frame is made of glass ceramics in which fillers are dispersed in borosilicate glass. The borosilicate glass and the filler both contain aluminum oxide. The volume fraction of the filler in the glass ceramic is 40 to 65%, The volume fraction of the aluminum oxide contained in the filler in the glass ceramic is 10 to 65%, The absolute value of the difference between the average thermal expansion coefficient of the flat glass and the outer frame at 50 to 350°C is 20×10 -7 / ℃ below.

2. The framed cover glass according to claim 1, wherein: The maximum height roughness Rz of the surface of the outer frame located on the side opposite to the flat glass side is 5 μm or less.

3. The framed cover glass according to claim 1, wherein: The softening point of the glass adhesive layer is lower than the softening point of the borosilicate glass. The softening point of the glass adhesive layer is lower than the glass transition temperature Tg of the flat glass.

4. The framed cover glass according to claim 3, wherein: The glass bonding layer comprises bismuth-based glass, vanadium-based glass, or borosilicate-based glass. The thickness of the glass adhesive layer is 10 to 30 μm.

5. The framed cover glass according to claim 1, wherein: The height of the outer frame is 350 μm to 4 mm.

6. The framed cover glass according to claim 1, wherein: The flat glass has a light diffusion portion on the first main surface. The light diffusion portion is formed by directly processing the flat glass.

7. The framed cover glass according to claim 6, wherein: The light diffusion portion is formed inside a region to which the outer frame is bonded.

8. The framed cover glass according to claim 1, wherein: The flat glass has a conductive film on the first main surface. A metal conductor is provided inside the outer frame, penetrating the outer frame and arranged perpendicularly to the flat glass. The conductive film is electrically connected to the metal conductor.

9. The framed cover glass according to claim 2, wherein: The outer frame further has a sealing material layer on a surface on the side opposite to the flat glass side. The sealing material layer is composed of a metal film or glass frit.

10. The framed cover glass according to claim 9, wherein: The sealing material layer is composed of a metal film, The metal film has an Ag layer or an Au layer on its outermost surface.

11. A semiconductor light emitting device comprising: the cover glass with a frame according to claim 10, a substrate, and a light emitting element provided on the substrate, The cover glass with a frame is integrated with the substrate via the sealing material layer and the gold tin ring in the cover glass with a frame, and the light emitting element is hermetically sealed.

12. A semiconductor light receiving device comprising: the cover glass with a frame according to claim 10, a substrate, and a light receiving element provided on the substrate, The cover glass with a frame is integrated with the substrate via the sealing material layer and the gold tin ring in the cover glass with a frame, and the light receiving element is hermetically sealed.

Citation Information

Patent Citations

  • Furnace wall cooler

    JP1981046981A

  • Organic electroluminescent element and method for manufacturing the same

    JP2013222522A

  • Synthetic quartz glass cavity, synthetic quartz glass cavity lid, optical device package, and method for manufacturing them

    JP2020021937A

  • Information processing system, information processing method, and information processing program

    JP2022122179A

  • Cover glass with outer frame, semiconductor light-emitting device, and semiconductor light-receiving device

    WO2022138519A1